Bridging the gap: A qualitative insight into the role of social entrepreneurship in empowering minorities - Andriyani, Andriyani; Lasta, Gracy Adira; Hasya, Afina (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
Social entrepreneurship has emerged as a viable approach of addressing the challenges faced by social minorities. Despite its growing importance, there is a lack of understanding of the factors that affect social entrepreneurs and their approaches to creating social value. This study aims to narrow this gap by examining the fundamental factors influencing the rise of social entrepreneurs, value creation processes, and the role of social entrepreneurship in addressing minority issues. The study used a qualitative, phenomenological approach and purposeful sampling to choose four informants who each had their own unique and representative traits. Data were collected through semi-structured interviews and validated through documentary analysis. The findings indicate that the motivations for social entrepreneurship stem from both external and internal factors. Nevertheless, social entrepreneurs consistently prioritize social objectives as their primary focus. Research reveals that resource constraints often impede value creation in social entrepreneurship, hence postponing progress. Despite all the obstacles, social entrepreneurship has immense benefits for the entrepreneurs themselves and for the communities they want to reach out to. The results also show that larger impacts could have been achieved by social entrepreneurs through refinements in their business strategies, creative solutions to social problems, good relationships with stakeholders, and ensuring financial sustainability of the venture.